Antiherpevirus activity of Artemisia arborescens essential oil and inhibition of lateral diffusion in Vero cells - Casu Laura; Chisu Lorenza; Cottiglia Filippo; Sanna Adriana; Saddi Manuela; Bonsignore Leonardo; De Logu Alessandro (BMC, 2007)
Abstract Background New prophylactic and therapeutic tools are needed for the treatment of herpes simplex virus infections. Several essential oils have shown to possess antiviral activity in vitro against a wide spectrum of viruses. Aim The present study was assess to investigate the activities of the essential oil obtained from leaves of Artemisia arborescens against HSV-1 and HSV-2 Methods The cytotoxicity in Vero cells was evaluated by the MTT reduction method. The IC50 values were determined by plaque reduction assay. In order to characterize the mechanism of action, yield reduction assay, inhibition of plaque development assay, attachment assay, penetration assay and post-attachment virus neutralization assay were also performed. Results The IC50 values, determined by plaque reduction assay, were 2.4 and 4.1 μg/ml for HSV-1 and HSV-2, respectively, while the cytotoxicity assay against Vero cells, as determined by the MTT reduction method, showed a CC50 value of 132 μg/ml, indicating a CC50/IC50 ratio of 55 for HSV-1 and 32.2 for HSV-2. The antiviral activity of A. arborescens essential oil is principally due to direct virucidal effects. A poor activity determined by yield reduction assay was observed against HSV-1 at higher concentrations when added to cultures of infected cells. No inhibition was observed by attachment assay, penetration assay and post-attachment virus neutralization assay. Furthermore, inhibition of plaque development assay showed that A. arborescens essential oil inhibits the lateral diffusion of both HSV-1 and HSV-2. Conclusion This study demonstrates the antiviral activity of the essential oil in toto obtained from A. arborescens against HSV-1 and HSV-2. The mode of action of the essential oil as antiherpesvirus agent seems to be particularly interesting in consideration of its ability to inactivate the virus and to inhibit the cell-to-cell virus diffusion.